Pulmonary hypertension in the connective tissue disease pathogenesis, clinical features and therapeutic options in 2006 - Asherson, Ronald (Henry Stewart Talks, 2007)
Diagnosis of pulmonary arterial hypertension (PAH), Classification of the types of PAH, Pathogenesis, Role of endothelin 1, Role of prostacyclin/thromboxane, Role of antiphospholipid antibodies, CD4 cells and PAH in HIV infection and autoimmune diseases, PAH in SLE, systemic sclerosis and CREST syndrome, Rheumatoid arthritis, Sjogren's syndrome, Autoimmune aspects of "primary" idiopathic PAH, Clinical manifestations of PAH, Thromboembolic PAH, New therapies with endothelin 1 antagonists (non-selective and selective), prostacyclin analogues (inhaled and IV) and phosphodiesterase inhibitors (e.g. sildenafil)
Archived at 2018/05/31